Genetic Diversity and Virulence Factors of S. aureus Isolated from Food, Humans, and Animals - Roberto Adame-Gómez; Natividad Castro-Alarcón; Amalia Vences-Velázquez; Jeiry Toribio-Jiménez; Abigail Pérez-Valdespino; Marco- Antonio Leyva-Vázquez; Arturo Ramírez-Peralta (International Journal of Microbiology)
Staphylococcus aureus is a commensal bacterium in humans and animals able to adapt to multiple environments. The aim of this study was to compare the genetic diversity and virulence profiles of strains of S. aureus isolated from food (29 strains), humans (43 strains), and animals (8 strains). 80 lipase-producing strains belonging to a biobank of 360 isolates, identified phenotypically as S. aureus, were selected. Confirmation of the species was made by amplifying the spA gene and 80% (64/80) of the strains were confirmed within this species. The virulence profile of each of the isolates was determined by PCR. The seA gene coding for enterotoxin A was found in 53.1% of the strains, the saK gene, which codes for Staphylokinase, was amplified in 57.8% of the strains, and, finally, the hlB gene coding for β-Hemolysin was amplified in 17.2%. The profile of antimicrobial resistance was determined by the Kirby Bauer method showing that the strains from food presented greater resistance to erythromycin (40.7%) and ciprofloxacin (18.5%) while in strains isolated from humans were to erythromycin (48.4%) and clindamycin (21.2%). Also, in strains from animals, a high resistance to erythromycin was observed (75%). The frequency of MRSA was 12.5% due to the presence of the mec gene and resistance to cefoxitin. Of the total strains, 68.7% were typed by PCR-RFLP of the coa gene using the AluI enzyme; derived from this restriction, 17 profiles were generated. Profile 4 (490 bp, 300 bp) was the most frequent, containing a higher number of strains with a higher number of virulence factors and antimicrobial resistance, which is associated with greater adaptation to different environments. In this study, a wide genetic diversity of strains of S. aureus from different foods, humans, and animals was found. This demonstrates evolution, genetic versatility, and, therefore, the adaptation of this microorganism in different environments.